Sort by

- Relevance
- |Time

...the transistor emitter current is I*Rs/100 (100 ohm resistor at top

**LHS**of diagram.) For large current gains in the transistor, the collector current...1 Answers · Science & Mathematics · 16/06/2015

...x'ing b.s. by 2 / 300x10^-9 ] ⇒ √ 123.3 = V ... evaluating

**LHS**and taking square roots of b.s. ] ⇒ V ≅ 11 V (b...1 Answers · Science & Mathematics · 28/09/2014

r(t) = e^-t costi + e^-t sintj + e^-tk This shows that point (x, y, z) is parametrically (e^-t cost, e^-t sint, e^-t)

**LHS**= z^2= e^2t RHS= x^2 + y^2= e^2t( cos^2t + sin^2t )= e^2t So vector lies on cone1 Answers · Science & Mathematics · 25/09/2014

...st) ] dt ADD the integral from the RHS to the original integral on the

**LHS**, obtaining: [1 + (a^2/s^2)] * F(s) = 1/s + [(a/s^2)*(sin at)*e^(-st...3 Answers · Science & Mathematics · 11/08/2014

1. Simplify the given equation. 2. Move all the unknowns(usually the subject) on your

**LHS**and the rest of the known values on the RHS 3. Equate them to get the answer.1 Answers · Science & Mathematics · 17/03/2014

...u(x) to get u(x)y' + P(x)u(x)y = u(x)g(x) Notice that the

**LHS**becomes an exact differential, d(u(x)y). Given: y dx - 4(x + y^6...1 Answers · Science & Mathematics · 18/02/2014

(5 - 2x) dy - 2y dx = 0 M_y = -2, N_x = -2. The

**LHS**is the exact differential of f(x,y) = 5y - 2xy, so the general solution is...1 Answers · Science & Mathematics · 13/02/2014

...sec(3x)*tan(3x) Since M_y is not equal to N_x, the

**LHS**of the equation is not an exact differential, and some other method of solution woulld...1 Answers · Science & Mathematics · 13/02/2014

...x(t-to)) which is equal to y(t-to)(replace t by to in the RHS and

**LHS**of the equation y(t-to) = = sin(x(t-to))). It is obvious from the relation...1 Answers · Science & Mathematics · 28/01/2014

... / (EI) ==> M = y'' EI Looking at the

**LHS**of the Beam P/2 ======= P ======= P/2 | ------ x...1 Answers · Science & Mathematics · 16/01/2014